2023
DOI: 10.3390/ijerph20054071
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and COVID-19 in University Students: Findings from a Qualitative, Comparative Study in Italy and the UK

Abstract: Introduction: COVID-19 restrictions introduced several changes in university academic and social experience. Self-isolation and online teaching have amplified students’ mental health vulnerability. Thus, we aimed to explore feelings and perspectives about the impact of the pandemic on mental health, comparing students from Italy and the UK. Methods: Data were collected from the qualitative portion of “the CAMPUS study”, longitudinally assessing mental health of students at the University of Milano-Bicocca (Ita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 91 publications
(122 reference statements)
0
19
0
Order By: Relevance
“…Reports from universities in the USA and France revealed that females were more likely to display distress and negative emotions during the COVID-19 period [ 10 , 11 ]. A qualitive, comparative study in Italy and the UK revealed additional risk factors that should be considered [ 12 ]. More specifically, it was observed that uncertainty about the future is a major stressor in young adults, alongside financial hardship and educational instability [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports from universities in the USA and France revealed that females were more likely to display distress and negative emotions during the COVID-19 period [ 10 , 11 ]. A qualitive, comparative study in Italy and the UK revealed additional risk factors that should be considered [ 12 ]. More specifically, it was observed that uncertainty about the future is a major stressor in young adults, alongside financial hardship and educational instability [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A qualitive, comparative study in Italy and the UK revealed additional risk factors that should be considered [ 12 ]. More specifically, it was observed that uncertainty about the future is a major stressor in young adults, alongside financial hardship and educational instability [ 12 ]. Additionally, students who needed psychological support before and during the pandemic were at higher risk [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the mandatory army conscription in Israel among the Jewish population, the average age of university students tends to be older than in countries without mandatory army conscription (Organization for Economic Co-operation and Development, 2022). This is reflected in the current study as the average age of our sample was older than in other studies assessing the impacts of the pandemic on university students (e.g., Riboldi et al, 2023;Rogowska et al, 2020;, which limits the generalizability of our findings.…”
Section: Limitationsmentioning
confidence: 72%
“…Other research has found that COVID‐19‐related concerns were directly related to depression and anxiety (Bitan et al, 2020; Commodari et al, 2021; Faisal et al, 2021; Reznik et al, 2021; Schiff et al, 2021; Wathelet et al, 2020), and that loss in resources during the pandemic was directly related to depression and anxiety (Ehmke et al, 2022; Riboldi et al, 2023; Voltmer et al, 2021). To the best of our knowledge, the current study appears to be the first to show the indirect pathways between these variables.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation